REAKTUALISASI KONSEP DASAR PENDIDIKAN ISLAM: PARADIGMA BARU DI ERA MASYARAKAT EKONOMI ASEAN (MEA) DALAM PELUANG DAN TANTANGAN - Surawadi Surawadi; Awad Awad (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2021)
In this era of globalization, it is necessary for the modernization process to occur in human life, due to the fulfillment of various human demands and the development of advances in the fields of science and technology, especially in the world of information and new innovations that bring drastic changes. Facing such a situation, Islamic education must also try to put its position into a strategic position not only in the context of building a complete human being, but also instilling ideal values for the life and progress of a dynamically developing society so that it can provide solutions to various problems that arise arise as a result of advances in science and technology, modernization and globalization. In addition, Islamic education is also expected to be able to build an integrative scientific and technological style construction (between spiritualism and realism) in life. Education is also the best institution in guiding human life to realize its self-actualization for a full and prosperous life in accordance with the ideals of life. All of this, of course, cannot be separated from the concept of divinity, humanity and nature which was developed in an integrative way.Keywords: Reactualization of Islamic Education, New Paradigm